2018
DOI: 10.1007/s11010-018-3334-8
|View full text |Cite
|
Sign up to set email alerts
|

MCAM knockdown impairs PPARγ expression and 3T3-L1 fibroblasts differentiation to adipocytes

Abstract: We investigated for the first time the expression of melanoma cell adhesion molecule (MCAM) and its involvement in the differentiation of 3T3-L1 fibroblasts to adipocytes. We found that MCAM mRNA increased subsequent to the activation of the master regulator of adipogenesis, PPARγ, and this increase was maintained in the mature adipocytes. On the other hand, MCAM knockdown impaired differentiation and induction of PPARγ as well as expression of genes activated by PPARγ. However, events that precede and are nec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 41 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…Another study found that CD146+ human placenta‐derived MSCs had identical chondrogenic or adipogenic differentiation potential compared with the CD146− cells . However, CD146 KO impaired adipogenic differentiation in 3T3‐L1 fibroblasts . The level of SSEA4 in human BMSCs or Wharton's Jelly‐derived MSCs did not correlate with either chondrogenic or adipogenic potential .…”
Section: Discussionmentioning
confidence: 99%
“…Another study found that CD146+ human placenta‐derived MSCs had identical chondrogenic or adipogenic differentiation potential compared with the CD146− cells . However, CD146 KO impaired adipogenic differentiation in 3T3‐L1 fibroblasts . The level of SSEA4 in human BMSCs or Wharton's Jelly‐derived MSCs did not correlate with either chondrogenic or adipogenic potential .…”
Section: Discussionmentioning
confidence: 99%
“…Adipocytes are derived from mesenchymal stromal cells (MSCs), which are precursor cells that can differentiate to several lineages (e.g., osteocytes, chondrocytes, and adipocytes) [30]. 3T3-L1 fibroblasts are precursor cells used as a model to assess adipogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show loss of Gpr56 decreases 3T3‐L1 cell proliferation. Reduced cell adhesion inhibits adipogenesis (Gabrielli et al, ; Kamiya et al, ; Luo et al, ) and GPR56 is a member of the adhesion GPCR family that is involved in adhesion of various cell types including developing neurons, hemopoietic stem cells, and tumor cells (Koirala et al, ; Shashidhar et al, ; Saito et al, ). Here we show loss of Gpr56 reduces cell adhesion.…”
Section: Discussionmentioning
confidence: 99%